Vitamin B12 Status in Metformin Treated Diabetics: Cross Sectional Study - Thakur, Sanjay Kumar; Yadav , Shree Narayan; Dhakal, Sukhesh Purush; Supratik, Suman; Sah, Anil Kumar (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Metformin is the most commonly used drug for patients with type 2 diabetes mellitus (T2DM) patients. Metformin related vitamin B12 deficiency can cause anemia. According to various reports, Long-term metformin intake can cause malabsorption of vitamin B12 in almost 30% of patients. It may lead to lower levels of serum vitamin B12 concentration in 14% to 30% of cases. Peripheral neuropathy may be a side effect of metformin induced vitamin B12 deficiency in patients with T2DM. Each 1000 mg/day of metformin dose increment increases the risk of vitamin B12 deficiency significantly. The longer is the duration of treatment with Metformin the higher is the risk of vitamin B12 deficiency.Method: Cross sectional Hospital Based observational Study. Patients attending to OPD and medical wards of National Academy of Medical Sciences, Bir Hospital were enrolled in this study. All T2 DM patients of the age group 20-80 years of both sex who were taking Metformin for a minimum of 3 months duration and at a dose of at least 1000mg/day. Determination of serum vitamin B12 level of the patients was determined using high performance liquid chromatography (HPLC) in bir hospital. vitamin B12 deficiency was categorized as a serum concentration of 300 pg/dl was considered as normal. Pearson’s chi-square tests were used to test the differences in the proportion of categorical variables, and independent t-tests was used for evaluating the difference between the means of two continuous variables. Pearson correlation analyses were performed to examine the linear relationship between serum vitamin B12 and metformin use. Receiver operator characteristic (ROC) curve analysis was used to evaluate the relationship between the duration of metformin use and vitamin B12 deficiency and to determine the reflection point (cut-off value). The area under the curve (AUC) with 95% confidence interval (CI) was calculated. p-values 60 years of age (p-value =0.035) and in regular alcohol consumers (p-value =0.009) more often. Metformin dosage (p-value =0.102) or its duration (p-value =0.090) were not found statistically associated with vitamin B12 deficiency. Vitamin B12 deficiency was not significantly associated with Vegetarians (p-value =0.132) too.Conclusion: Vitamin B12 deficiency was found in 43.7% of diabetics who were treated with Metformin. The deficiency was significantly found among >60 years of age (p-value =0.035) who were regular alcohol consumers (p-value =0.009).